COMMUNITY-BASED TOURISM MODEL USING THE DEGREE OF CITIZEN POWER APPROACH - Zuhri, Ach; Rohmayati, Nita; Ridwan, Sihab; Omar, Siti; Aldi, Aldi (TRIKONOMIKA, 2025)
The purpose of this study was to determine the management of Bukit Tawap Nature Tourism based on Community-Based Tourism (CBT), and to develop a model with the Degrees of Citizen Power approach. This study is a type of participatory descriptive qualitative research using a participatory phenomenological approach and FGD approach, and was analyzed using Atlas.Ti software. The results found that the implementation of Bukit Tawap tourism is based on the spirit of cooperation of the community facilitated by the village government. The main challenge in managing CBT is changing the mindset and improving the coordination pattern between parties. The development of this model was made as an effort to adapt to local conditions and needs, as well as to build an institutional coordination framework between the village government and managers. The success of CBT management is highly dependent on multi-party collaboration and strengthening local capacity.